Sexual-related determinants of life satisfaction among married women: A cross-sectional study - Nasim Bahrami; Mobina Hosseini; Mark D. Griffiths; Zainab Alimoradi (BMC, 2023)
Abstract Background and aim Life satisfaction refers to the perceived satisfaction of individuals concerning various aspects of their lives. The present study investigated the predictive role of sexual-related determinants in life satisfaction among married women. Methods A cross-sectional study was conducted from August to November 2021. A total of 350 married women with at least six months of cohabitation with husbands were included in the study. The study utilized a multi-stage random sampling method from 10 comprehensive health centers in Qazvin, Iran. Scores on the Emotional Intimacy Questionnaire (EIQ), Dyadic Sexual Communication Scale (DSCS), Female Sexual Distress Questionnaire (FSDQ), Female Sexual Quality of Life Scale (FSQLS), Female Sexual Function Index (FSFI), and Life Satisfaction Scale (LSS) were assessed. Data were analyzed using univariable and multivariable linear regression models with a significance level of p < 0.05. Results The mean age of participants was 33.77 years (SD = 9.77) and they had been married for an average of 10.21 years (SD = 9.93). The mean scores on the LSS were 20.16 (out of 35; SD = 6.79). Based on the multivariable linear regression model adjusted for socio-demographic characteristics, the two strongest predictors of life satisfaction among Iranian married women were marital intimacy (β = 0.49, p < 0.001) and sexual functioning (β = 0.17, p = 0.009). Together, these variables explained 45% of variance in life satisfaction. Conclusion Given that marital intimacy and sexual functioning were the most significant sexual-related determinants of life satisfaction among married women, designing and implementing interventions which increase women's marital intimacy and sexual functioning might improve married women's life satisfaction.